ANALISIS INOVASI PELAYANAN PUBLIK PROGRAM KIOS 3 IN 1 DI BALAI LATIHAN KERJA DAN PENGEMBANGAN PRODUKTIVITAS DIY - Murdapa, Purnama Andri; Najib, Khoiri; Priyanti, Luluk; Hapsari, Cinthia Mutiara (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
In the modern era of today, kios 3 in 1 is a service provided for employment, where one of them through work training halls and development of productivity of BLKPP DIY.Work training halls and productivity development are an appropriate institution in empowerment of society, because BLKPP DIY provides work skills training with a wide range of programs.The concept used by Kios 3 in 1 is the form of a development system of SDM or where the labor utilizes software or technological systems that can improve the relations between governments and other parties of society. energy of effort, the world, as well as in the field of workforce training, Working training halls throughout Indonesia have become the point of point in implementation of the 3 in 1 system.The 3 in 1 concept was then facilitated by the Ministry of Workforce through the 3 in 1 kios application available.The research method used in this study is a qualitative descriptive, where it was obtained.